Experimental Study on Lateral Bearing Mechanical Characteristics and Damage Numerical Simulation of Micropile - Ning Liu; Yi-Xiong Huang; Bo Wu; Wei Huang (Advances in Civil Engineering)
The construction site of the foundation pit support project in the urban area is narrow. Micropile has the advantages of flexible pile position layout, strong site adaptability, and fast construction speed, which can effectively control the horizontal displacement of the foundation pit and ensure the safety of surrounding buildings. However, the lateral bearing capacity of micropile is weak. In order to study the lateral force characteristics and failure characteristics of micropile, laboratory tests on the flexural and tensile strength of reinforced concrete micropiles with different diameters and with or without external steel pipes were performed. The authors studied the lateral force characteristics and failure characteristics of various types of micropiles. Based on numerical simulation software ABAQUS, the measured yield strength of the specimen was used as the loading force. And taking the occurrence and development of concrete damage into consideration, the loading process was simulated. The result shows the following: (1) the micropile specimens with external steel pipe had better flexural performance than the bare micropiles and the mechanical characteristics of the specimens changed from brittleness to plasticity; (2) the degree of concrete damage is greatly reduced after the external steel pipe is attached, and the bearing capacity of the micropile specimen of the same diameter is increased by 70% after the external steel pipe is added; and (3) the specimens were mainly damaged due to tensile damage. The calculation formula for the lateral bearing capacity of the concrete-filled steel tube micropile considering the damage is proposed through fitting analysis. The calculation formula, the finite element calculation value, and the calculation formula proposed by other scholars are compared with the authors' test and the test data of other scholars. The meta-calculation results, experimental results, and formula calculation results proposed by the authors have high accuracy.